Przesłanki wykorzystania marketingu partnerskiego w sektorze turystycznym - Panasiuk, Aleksander (Concepts for Taking Advantage of Partnership Marketing in the Sector of Tourism, 2005)
This paper presents concepts referring to problems of introducing partnership marketing principles into the sector of tourism. There are described basics concepts of services marketing, starting from external and internal marketing, through an interaction marketing, and finishing with new marketing concepts, referred to as partnership marketing, clienting or relationship marketing. The entities of tourism sector, which should participate in tasks resulting from the objectives of partnership marketing, were pointed to, and potential areas of utilising the mentioned above concepts were explained in a synthetic way. The basic concept, resulting from practical application opportunities for the discussed issues, is the integration of activities performed by a broad group consisting of the participants of tourist market, who are represented by the tourist branch, local self-government units, economic entities, local and regional tourist organisations and the client (the tourist) him/herself.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1074, s. 80-90